Senecio scandens Buch.-Ham. polysaccharides exert anti-atopic dermatitis effects by modulating gut microbiota and the MAPK/NF-κB pathway - Hu, Zhi-Qin; Xie, Shu-Shu; Zhou, Ming-Yuan; Chen, Yu-Chi; Zhou, Fang-Mei; Ding, Zhi-Shan; Ye, Xiao-Qing (Frontiers in Pharmacology, 2025)
This study aims to extract polysaccharides from Senecio scandens Buch.-Ham. (SSP) using alcohol and water extraction and investigate whether they can be delivered orally to treat atopic dermatitis (AD). In vivo investigations demonstrated that SSP notably improved inflammation in mice, reducing ear swelling, scratching frequency, mast cell infiltration, and epidermal thickness. Furthermore, it lowered the levels of associated inflammatory markers, increased the production of skin barrier-associated proteins, and restored gut microbial diversity, which altered the composition of bacterial communities. In vitro experiments demonstrated that SSP could diminish the levels of inflammatory factors in the human immortal keratinocyte line (HaCaT) and suppress the MAPK/NF-κB signaling pathway. Our results suggest SSP exerts anti-AD effects and regulates the gut–skin axis in mice. The anti-inflammatory mechanism involves the MAPK/NF-κB signaling pathway. It is being tested for development into an effective drug for AD.